Future Scenario of Global Climate Map change according to the Köppen -Geiger Climate Classification - fahmy Osman Mohammed; Anwar Othman Mohammad; Hivi Shawket Ibrahim; Rozhgar Abdullah Hasan (مجلة بغداد للعلوم)
Earth’s climate changes rapidly due to the increases in human demands and rapid economic growth. These changes will affect the entire biosphere, mostly in negative ways. Predicting future changes will put us in a better position to minimize their catastrophic effects and to understand how humans can cope with the new changes beforehand. In this research, previous global climate data set observations from 1961-1990 have been used to predict the future climate change scenario for 2010-2039. The data were processed with Idrisi Andes software and the final Köppen-Geiger map was created with ArcGIS software. Based on Köppen climate classification, it was found that areas of Equator, Arid Steppes, and Snow will decrease by 3.9 %, 2.96%, and 0.09%, respectively. While the areas of Warm Temperature and Dessert will increase by 4.5% and 0.75%, respectively. The results of this study provide useful information on future climate Köppen-Geiger maps and areas that will most likely be affected by climate change in the following decades